2005
DOI: 10.1186/1472-6963-5-52
|View full text |Cite
|
Sign up to set email alerts
|

Effect on survey response rate of hand written versus printed signature on a covering letter: randomised controlled trial [ISRCTN67566265]

Abstract: Background: It is important that response rates to postal surveys are as high as possible to ensure that the results are representative and to maximise statistical power. Previous research has suggested that any personalisation of approach helps to improve the response rate. This experiment tested whether personalising questionnaires by hand signing the covering letter improved the response rate compared with a non-personalised group where the investigator's signature on the covering letter was scanned into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…22 There is conflicting data on the use of handwritten versus printed signatures on cover letters for mailout surveys. 7,23 Personalized cover letters and handwritten signatures were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…22 There is conflicting data on the use of handwritten versus printed signatures on cover letters for mailout surveys. 7,23 Personalized cover letters and handwritten signatures were used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The question of whether different methods of personalisation (such as hand-written signatures or including a participant's name on the cover letter) produce different effects on response was not examined. Recently, a randomised controlled trial and meta-analysis of previous trials found no advantage in hand-signed letters compared to those with photocopied or scanned signatures [ 3 ]. The study did not investigate the effect of using the participant's name, or using a hand-written signature and the participant's name together.…”
Section: Introductionmentioning
confidence: 99%
“…3 The overall response rate was similar to that of other questionnaire surveys. 12 Although there was variation in response to individual questions, the response rate to the questions on confidence and training was consistently high.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore set out to assess hospital traineesÕ perceptions of their skills and knowledge and of the amount of training they had received with regard to parameters set out in the ÔResource PackÕ. 12 Although there was variation in response to individual questions, the response rate to the questions on confidence and training was consistently high. 3 The overall response rate was similar to that of other questionnaire surveys.…”
Section: Discussionmentioning
confidence: 99%